Political Budget Cycle in Local Elections in Indonesia: A Systematic Review - Syam, Andi Armayudi; Afdal, Andi Ahmad Malikul (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
Political budget cycles (PBC) refer to patterns in which incumbents manipulate government budget policies in the run-up to elections to enhance their electoral chances. This article presents a systematic review of the recent literature on PBC in the context of regional elections in Indonesia. The review findings show that PBC at the local government level in Indonesia did occur significantly after the direct election era began. A number of empirical studies consistently find a pattern of increasing public spending and budget deficits in the years leading up to regional elections, especially in spending items that are visible and benefit voters (such as social assistance and local infrastructure projects). For example, social assistance and regional grant spending tend to increase drastically in election years, which contributes to a decrease in budget surpluses and an increase in short-term liabilities of local governments. This PBC is stronger when incumbent regents/mayors are running for re-election and when incumbents are supported by a large party coalition. On the other hand , the shift from indirect to direct elections at the regional level has been accompanied by a shift in spending patterns, including a decrease in capital spending around election periods. In terms of political effects, increased populist spending has been shown to be associated with higher incumbent vote acquisition, although this effect is influenced by the level of local electoral competition. Overall, the practice of political budget cycles in Indonesian regional elections signals challenges for fiscal accountability and the quality of local democracy.